2014
DOI: 10.7448/ias.17.4.19567
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of low bone mineral density among HIV patients on long‐term suppressive antiretroviral therapy in resource limited setting of western India

Abstract: IntroductionBone mineral density (BMD) assessment in HIV patients is sparsely done in resource limited settings.Materials and MethodsWe conducted a cross-sectional study of BMD amongst HIV patients following up in our clinic from 1 June to 1 December 2013 by performing dual-energy X-ray absorptiometry scan (Lunar Prodigy Advanced DXA System, GE Healthcare) of lumbar spine and hip. Patients on long term (≥12 months), virologically suppressive antiretroviral therapy (ART) were included. Patients who were ART naï… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 0 publications
2
17
0
1
Order By: Relevance
“…A comparable prevalence in reduced BMD (23%) was found by Cardeal et al (2017) among 108 individuals living with HIV in Brazil [23]. However, some studies have reported higher prevalence rates of reduced BMD ranging from 37% to 80% among PLWHIV [18][19][20]35]. A slightly lower prevalence in reduced BMD revealed in this study could be due to the age group of participants.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A comparable prevalence in reduced BMD (23%) was found by Cardeal et al (2017) among 108 individuals living with HIV in Brazil [23]. However, some studies have reported higher prevalence rates of reduced BMD ranging from 37% to 80% among PLWHIV [18][19][20]35]. A slightly lower prevalence in reduced BMD revealed in this study could be due to the age group of participants.…”
Section: Discussionsupporting
confidence: 80%
“…Higher prevalence rates of up to 85% of low BMD among PLWHIV in low and middle income countries have been reported by a number of studies [18][19][20][21][22]. Apart from ART, factors such as lack of physical activity (PA), lower body mass index (BMI), female sex, older age, nutritional deficiencies of calcium and vitamin D, depression, contraception use, smoking and alcohol use are believed to contribute to high prevalence of low BMD among PLWHIV [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In an abstract presented at the 2014 annual conference of the International AIDS Society (the only previous report from India), Dravid et al reported 29.6% and 36.6%, respectively, HAART naïve (n = 40) and on HAART patients (n = 496) to have osteoporosis [23]. However, details from that study are not available.…”
Section: Discussionmentioning
confidence: 99%
“…Brown et al 23 and Dravid et al 24 demonstrated how tenofovir-based regimens contributed to reduction in bone mineral density, together with HIV-related factors, such as low CD4+ count.…”
Section: Discussionmentioning
confidence: 99%